Tensile performance of braided composite rods for concrete reinforcement - Pereira, Cristiana Gonilho (2008)
The current work is concerned with the development of braided composite rods for civil engineering applications, namely for concrete internal reinforcement, as a steel substitute. The research study aims at understanding the tensile behaviour of composite rods reinforced by a textile structure – braided structure with core reinforcement. Seven types of braided composite rods were produced, varying the type of fibres used as a core reinforcement of a polyester braided structure. Eglass, carbon and HT polyethylene fibres were used in different combinations. The tensile properties of the braided reinforced composite rods were evaluated in order to identify the type(s) of fibre(s) to be used as core reinforcement. Results are compared to those of conventional materials used for concrete reinforcement, such as steel.